The critical study of non-religion: discourse, identification and locality - Cotter, Christopher R. (Bloomsbury Advances in Religious Studies, 2020)
"This book acts as a bridge between the critical study of 'religion' and empirical studies of 'religion in the real world'. Chris Cotter presents a concise and up-to-date critical survey of research on non-religion in the UK and beyond, before presenting the results of extensive research in Edinburgh's Southside which blurs the boundary between 'religion' and 'non-religion'. In doing so, Cotter demonstrates that these are dynamic subject positions, and phenomena can occupy both at the same time, or neither, depending on who is doing the positioning, and what issues are at stake. This book details an approach that avoids constructing 'religion' as in some way unique, whilst also fully incorporating 'non-religious' subject positions into religious studies. It provides a rich engagement with a wide variety of theoretical material, rooted in empirical data, which will be essential reading for those interested in critical, sociological and anthropological study of the contemporary non-/religious landscape."--